Untying the Knot : Making Peace in the Taiwan Strait - Bush, Richard C., 1947- (Book collections on Project MUSE., 2005)
"A comprehensive analysis of the paradoxical relationship between Taiwan and China, characterized by social and economic interaction and political and military tensions, and the diplomatic diffidence of the United States in the face of its high strategic stakes"--Provided by publisher.